Nutritional screening is strongly associated with overall survival in patients treated with targeted agents for metastatic renal cell carcinoma. Issue 3 (20th April 2015) - Gu, Weijie; Zhang, Guiming; Sun, Lijiang; Ma, Qi; Cheng, Yue; Zhang, Hailiang; Shi, Guohai; Zhu, Yao; Ye, Dingwei
Abstract: Background: Although commonly observed, malnutrition is poorly characterized and frequently underdiagnosed in patients with metastatic renal cell carcinoma (RCC). The ability of nutritional screening tools to predict overall survival (OS) in patients with RCC has not been adequately validated. The objective of this study was to investigate the performance of nutritional screening tools and their additional prognostic value in patients with metastatic RCC treated with targeted therapies. Methods: Patients were prospectively recruited from three tertiary hospitals between 2009 and 2013. Nutritional status was evaluated using the Geriatric Nutritional Risk Index (GNRI) and the Mini Nutritional Assessment–Short Form (MNA–SF). Their OS and early grade 3/4 adverse events were recorded as outcomes of interest, and their associations with nutritional status were assessed using Cox regression and logistic regression, respectively. The incremental value in prognostication was evaluated using concordance index and decision curve analyses. Results: Of the 300 enrolled patients, 95 (31.7%) and 64 (21.3%) were classified as being at risk of malnutrition according to the GNRI and MNA–SF, respectively. Both GNRI and MNA–SF were independent predictors of OS in multivariate analyses and provided significant added benefit to Heng risk classification. Compared with the MNA–SF, the GNRI contributed a higher increment to the concordance index (0.041 vs. 0.016). Nutritional screening, however, was not associated with early grade 3/4 adverse events in multivariate analyses. Further investigations are needed using more comprehensive and accurate assessment tools. Conclusions: This prospective study confirmed the importance of nutritional screening tools in survival prognostication in patients with metastatic RCC. The standardized and objective measurements would allow clinicians to identify metastatic RCC patients at risk of poor survival outcomes. Individualized nutritional assessment and intervention strategies may be included in the multidisciplinary treatment.